Pengaruh Pemberian Fungi MikorizaArbuskularTerhadapFaktorProduksidanHasilPadi (Oryza sativa L.) yang di TanampadaTinggiGenangan 10 cm di BawahPermukaan Tanah - Munawaroh, Madinah; Effendi, Arman; Ariani, Erlida (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
Arbuscularmycorrhizal fungi (FMA) is a soil microorganisms that form internal hyphae with plant roots producing phosphatase enzymes that are able to release P from specific bonds so that it can be absorbed by rice plants. This study aims to examine the effect of treating several doses of FMA and get the best dose to increase the results of rice plants (Oryza sativa L.) planted at a puddle height of 10 cm below the soil surface. This research is a complete randomized design trial consisting of five treatments and three replications, so that 15 experimental units. Each unit consists of five plants, so that 75 plants are obtained. All plants in each experimental unit are sampled. The treatments tested were several FMA doses consisting of no FMA, 15 g per plant, 30 g per plant, 45 g per plant, and 60 g per plant. The parameters observed were the number of productive tillers, panicle length, number of panicle branches, number of pithed grain per panicle, percentage of pithed grain, weight of 1000 grain of pithed grain, weight of dried milled grain per clump. Provision of AMF influences the yield of lowland rice. The provision of 45 g FMA per plant gave good results in increasing the number of productive tillers, panicle length, number of panicle branches and the weight of milled unhusked rice per clump. Keyword: Lowland rice, phosphatase, FMA, SRI Method